2011
DOI: 10.1007/s12272-011-0509-1
|View full text |Cite
|
Sign up to set email alerts
|

Improving the solubility and bioavailability of dihydroartemisinin by solid dispersions and inclusion complexes

Abstract: Dihydroartemisinin (DHA) is a poorly water-soluble drug that displays low bioavailability after oral administration. Attempts have been made to improve the solubility of DHA. Yet, no information is available concerning improved bioavailability. This study aimed to improve the water solubility of DHA by two systems: solid dispersions with polyvinylpyrrolidone (PVPK30, PVPK25, PVPK15) and inclusion complexes with hydroxypropyl-β-cyclodextrin (HPβCD), as well as improving the bioavailability of both systems. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
1
7
0
1
Order By: Relevance
“…As shown in Figure 1F, the cumulative release of ART was about 45.5% and DHA was about 42.9% over 24 h, which confirmed that the capacities of MNP to hold ART and DHA in physiological environment were similar. Actually, the solubility of DHA was slightly lower than ART, so during the first 2 h of the release process, ART exhibited a distinct rapid release behavior, which DHA didn't (Wang et al, 2007;Ansari et al, 2011). In addition, the cumulative release of AS reached 72.1% over 24 h, indicating that AS was more hydrophilic than ART and DHA, which was consistent with the reported work (Xu R.J. et al, 2019).…”
Section: Preparation and Characterization Of Drug-loaded Mnpsupporting
confidence: 88%
“…As shown in Figure 1F, the cumulative release of ART was about 45.5% and DHA was about 42.9% over 24 h, which confirmed that the capacities of MNP to hold ART and DHA in physiological environment were similar. Actually, the solubility of DHA was slightly lower than ART, so during the first 2 h of the release process, ART exhibited a distinct rapid release behavior, which DHA didn't (Wang et al, 2007;Ansari et al, 2011). In addition, the cumulative release of AS reached 72.1% over 24 h, indicating that AS was more hydrophilic than ART and DHA, which was consistent with the reported work (Xu R.J. et al, 2019).…”
Section: Preparation and Characterization Of Drug-loaded Mnpsupporting
confidence: 88%
“…Consequently, this enhanced the therapeutic effectiveness of artemisinin (Wong & Yuen, 2003b). These results were also played out in others studies using the derivatives of dihydroartemisinin (DHA), which in a complexation with HP-β-CD, equally improved the pharmacokinetic parameters when compared with DHA alone (Ansari, Batty, Iqbal & Sunderland, 2011). Artesunate in β-CD conjugates with a cytotoxicity against three types of human colon cancer cell lines (Jiang et al, 2014).…”
Section: Pharmacokineticsmentioning
confidence: 81%
“…As shown in Figure 1F, the cumulative release of ART was about 45.5 % and DHA was 226 about 42.9 % over 24 h, which confirmed that the capacities of MNP to hold ART and DHA in 227 physiological environment were similar. Actually, the solubility of DHA was slightly lower than ART, 228 so during the first 2 hours of the release process, ART exhibited a distinct rapid release behavior, which 229 DHA didn't (Wang et al, 2007;Ansari et al, 2011). In addition, the cumulative release of AS reached 230 72.1 % over 24 h, indicating that AS was more hydrophilic than ART and DHA, which was consistent 231…”
Section: Preparation and Characterization Of Drug-loaded Mnp 201mentioning
confidence: 84%